Role of Teachers as Motivators in Learning Islamic Religious Education in Elementary School of Negeri 05 Pontianak Timur - Rianawati, Rianawati; Mentari, Diah; Maruf, Maruf; Tursina, Nani (Universitas Malikussaleh, 2020)
Motivation is the self-driving power of students to learn on an ongoing basis. Furthermore, motivation has a particular position to achieve goals. Therefore, without motivation, the learning process will not go well. Nowadays, often the social environment and the development of modern life affect student learning motivation. Because of that, the optimal role of the teacher is needed to foster student learning motivation. This study aims to determine 1) The purpose of the teacher as an intrinsic motivator of student learning in Islamic Religious Education Subjects in SD Negeri 05 Timur Pontianak (Elementary Schools). 2) The purpose of the teacher as a motivator for extrinsically learning students in Islamic Religious Education subjects at SD Negeri 05 Timur Pontianak. This type of research is qualitative research. Data collection techniques through in-depth interview techniques and participatory observation techniques. Based on the analysis results, the findings of this study are: 1) The role of the teacher as intrinsic learning motivator in students is done by increasing the desire of students to acquire skills in learning, obtaining information about science, hopes of achievement (academic and non-academic achievements) desire to be the best and hope to be accepted by parents.